Improving the Students’ Speaking Skill through Talking Stick Strategy at the Tenth Grade of SMK Negeri 2 Gunungsitoli in 2022/2023 - Candiawan Telaumbanua; Elwin Piarawan Zebua; Afore Tahir Harefa; Kristof Martin Efori Telaumbanua (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
There were some problems that students faced when speaking, such as: difficult in conveying their ideas, lack of vocabulary, incorrect pronunciation, and the strategy that used by the teacher that monotonous and boring. The purpose of this research was to improve the students' speaking skills through Talking Stick Strategy at the tenth grade of SMK Negeri 2 Gunungsitoli in 2022/2023. The researcher conducted this research by using Classroom Action Research (CAR). Instrument of the research were observation sheets, field notes and oral test. In Cycle I, the average percentage of the researcher's completed activities was 79% (good), and the percentage of the students' completed activities was 72.5% (adequate). In this cycle, the students could not achieve the Minimum Competence Criterion (MCC) of 70, students' average score was 51 (less). All the students scored ≤ 70, with the highest score was 63 and the lowest score was 38. Furthermore, in Cycle II, the average percentage of the researcher's completed activities was 95% (very good), and the students' completed activities was 91% (very good). In this cycle, the students had achieved the Minimum Competence Criterion (MCC) of 70, the students' average score was 79 (good). None of the students scored ≤ 70, with the highest score was 81 and the lowest score was 75. Based on the results of this research, the researcher concluded that Talking Stick Strategy could improve the students' speaking skill in the tenth grade of SMK Negeri 2 Gunungsitoli in 2022/2023.